Luces y sombras en la inserción laboral de los inmigrantes latinoamericanos en España - Pablo Pumares-Fernández (Mélanges de la Casa de Velázquez)
Latin Americans have constituted the main contingent in the burgeoning of immigration to Spain since 2000. Encouraged during the second Partido Popular government (2000-2004) and driven by economic crisis in the cases of Ecuador and Argentina, Spain offered them an attractive destination where sustained economic growth gave them the chance to find work. Although one of the more recent immigrant waves, they have found integration in the labour market easier than other foreign groups. For example the fact that they speak Spanish has made it easier for them to find work in the services sector, and in some cases even in public employment. They are likewise a strong presence in the General Social Security Scheme and the Special Scheme for Domestic Employees. This last segment is especially important as a means of entry to the labour market, but there is also a high rate of transfer to the General Scheme, which clearly offers an improvement in working conditions.